Semisubmersible offshore structure in an extreme wave domain with itinerant ice pieces - Zaman, Hasanat; Akinturk, Ayhan (Oceans 2020 Conference, 2020)
Presence of nomadic ice pieces of various sizes in the North Seas such as, in the Grand Bank area of Newfoundland and Labrador largely inflicts extra threats to the operations and stability of semisubmersible offshore structures (SOS). During stormy weather or in a situation of very large waves, the operation and safety of such SOS are extremely risked when ices pieces propagating alongside with the heavy waves. This paper reports initial findings for the effects of various large waves on the risk of occurrence and severity of ice pieces and topside collisions. OrcaFlexᵀᴹ is a commercial code utilized in this project as the numerical simulator. This is a 3D non-linear time-domain finite element implicit and explicit code that utilizes lumped mass elements to simplify equations and to enhance computational efficiency. The results obtained from the OrcaFlex code are compared with the results predicted by StarCCM+ full scale dispersive commercial code for an alike case. The comparisons of the data show a valuable data match. Peer reviewed: Yes NRC publication: Yes